PERANCANGAN ARSITEKTUR ENTERPRISE SISTEM INFORMASI AKADEMIK SMK IBRAHIMY 1 SUKOREJO MENGGUNAKAN METODE TOGAF - Akhlis Munazilin; Diana Uzlifatil Khairu Ummah; Fitri Elvi Karisma (CV. Denasya Smart Publisher, 2025)
The growing reliance on information technology in educational management has encouraged institutions to reorganize academic services in a more structured, accurate, and integrated manner. SMK Ibrahimy 1 Sukorejo faces similar challenges, as most academic processes are still carried out partially and are not supported by a standardized information system. This condition leads to data duplication, inefficient workflows, and delays in providing information to stakeholders. This study aims to design an enterprise architecture for the Academic Information System (AIS) that serves as a structured and sustainable guideline for academic system development. A descriptive qualitative approach was employed using the TOGAF framework through the stages of the Architecture Development Method (ADM). Data were collected through interviews, observations, and document analysis within SMK Ibrahimy 1 Sukorejo. The results indicate that the proposed architecture successfully maps academic business processes comprehensively, identifies data and application requirements, and formulates a technology architecture aligned with the school’s operational needs. The resulting architectural blueprint is expected to provide a foundation for developing an integrated and adaptive Academic Information System that supports the enhancement of educational service quality at SMK Ibrahimy 1 Sukorejo.